2013
DOI: 10.1007/978-3-642-39459-1_13
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-symmetric Group Algebras and C ∗-Completions of Hecke Algebras

Abstract: We show that for a Hecke pair (G,Γ ) the C * -completions C * (L 1 (G,Γ )) and pC * (G)p of its Hecke algebra coincide whenever the group algebra L 1 (G) satisfies a spectral property which we call "quasi-symmetry", a property that is satisfied by all Hermitian groups and all groups with subexponential growth. We generalize in this way a result of Kaliszewski, Landstad and Quigg [11]. Combining this result with our earlier results in [14] and a theorem of Tzanev [17] we establish that the full Hecke C * -algeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Indeed, we prove the result in much greater generality. The proof differs from the case of n = 2 in [14] in that it appeals to property (T). After the second named author's talk on the case n = 2 at a NordForsk conference on the Farøe Islands in 2012, a discussion with M. Landstad revealed that the obstruction to injectivity in the case n = 3 would be property (T).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Indeed, we prove the result in much greater generality. The proof differs from the case of n = 2 in [14] in that it appeals to property (T). After the second named author's talk on the case n = 2 at a NordForsk conference on the Farøe Islands in 2012, a discussion with M. Landstad revealed that the obstruction to injectivity in the case n = 3 would be property (T).…”
Section: Introductionmentioning
confidence: 88%
“…see [21] and [10]. This map is known to be an isomorphism in many cases, such as when G is Hermitian, [10], or when L 1 (G) is quasi-symmetric in the terminology of [14]. The last property is known to hold for a class of groups containing Hermitian groups and groups with subexponential growth.…”
Section: Generalities About Spherical Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These questions have already been asked by the author in [13], and the groups in questions 1) and 2) are natural to be considered in this regard. A negative answer to this question would imply that all Hermitian totally disconnected groups are amenable, which would give more evidence to the following long standing conjecture (see [14]):…”
Section: Some Questionsmentioning
confidence: 99%